1154 The Effect Of COVID-19 Pandemic on Mortality Rates in General Surgery in A District General Hospital. (12th October 2021) - Bhattacharya, P; Mobarak, D
Abstract: Introduction: WHO declared COVID-19 to be a global pandemic on March 11th 2020. It has has a profound on health care delivery and allocation of resources. Aim: To find out the effect of the COVID-19 pandemic on mortality rates of patients admitted under general surgery in our hospital. Method: Retrospective data collection of deaths in all inpatients from March to November 2020 (group A)and comparing it with data collected on inpatients from March to November 2019( Group B). Results: There were 46 deaths out of 3534 admissions in group A compared to 55 deaths out of 6576 admissions in group B. This meant a rise of mortality from 0.84% in 2019 to 0.94 % in 2020, this is a statistically significant result (p = 0.02). The median age of mortalities in 2020 is 81.5 vs 79 years in 2019 and median documented interval between onset of symptoms to presentation in hospital was 2 days in 2020 as it was during 2019. Perforations accounted for more than half of 2020 deaths ( 29 out of 46) and 6 patients out of 46 were COVID-19 on swab testing. Conclusions: 1. COVID-19 has had a significant impact on mortality rates in general surgery in 2020. 2. Perforations account for a majority of deaths, as evidenced by mean time to presentation at hospital; this may be attributed to delayed seeking of healthcare facilities as a result of lockdown. 3. Public education is required to seek medical attention early to improve outcomes of serious surgical conditions.